Preditores da habilidade de caminhar independente de indivíduos pós acidente vascular cerebral: um estudo longitudinal - Nathalia Aparecida Gravito Rodrigues (2022)
Stroke is considered one of the main causes of disability. Despite the increase in post-stroke lifespan, there is an increase in the number of people who have survived stroke with disabilities, which include impairments in body structure and function, in addition to activities and restriction. More than halfof the strokepatients suffer from limitations in the ability to walk independently, affecting their involvement in activities of daily living and social participation. The use of predictors has been emphasized in clinical practice as a tool for planning and supporting clinical decision-making. The use of prognostic information regarding post-stroke mobility, still during acute care, can be helpful in planning hospital discharge, establishing adequate therapeutic goals, and reducing care costs. Therefore, the objectives of the present study are: i) to develop predictive equations for the ability of walking independently in post-stroke patients at three and six months after the event; ii) to analyze the accuracy of the equations for predicting independent at three and six months. This is a prospective cohort study carried out at the Cerebral Vascular Accident Unit (CVA) of Hospital Risoleta Tolentino Neves (HRTN). In the period between 09/23/2019 and 02/26/2021, 384 people were admitted to the U-AVC/HRTN who met the inclusion criteria: clinical diagnosis of primary stroke, with diagnostic confirmation through neuroimaging analysis and age ≥20 years. Individuals who had a history of previous disability and/or the occurrence of other previous musculoskeletal or neurological conditions were excluded. The baseline assessment (T0) was performed during hospitalization, and the follow-up assessments at three (T1) (n=263) and six months (T2) (n=212) post-stroke were performed via telephone contact. Participants were randomly allocated to either the equation development groups or the confirmatory groups. The independent variables collected during hospital stay were: age (years), residual deficit in knee extensor muscle strength (manual dynamometer), motor function (Fulg Meyer Scale - Lower limb motor function), neglect (National Institutes of Health Stroke Scale – item 11), continence (Functional Independence Measure – items G and H) and independence in ADL (Modified Barthel Index - MBI). The outcome variable, ability to walk independently, was assessed using the Functional Ambuylatory Categories (FAC), applied via telephone contact at three and six months. Longitudinal linear regression models were fitted to identify potential predictors of the ability to walk independently at 3and 6 months post-stroke, defining the equations from these models. Predictive accuracy was analyzed in the confirmatory group. At three months post-stroke, linear regression analysis in the model development group (n=173) resulted in the following predictor equation: y=3.040+(0.283 x FAC baseline)+(0.021x MBI). The accuracy analysis (n=90) indicated: sensitivity (0.90), specificity (0.57), accuracy (0.77), positive predictive value (0.76) and negative predictive value (0.80). At six months post-stroke, in the model development group (n=141), the following predictor equation was developed: y=3.644+(-0.014 x age)+(0.014 x IBM). The accuracy analysis (n=71) indicated: sensitivity (0.54), specificity (0.81), accuracy (0.62), positive predictive value (0.87) and negative predictive value (0.42). Performing these simple tests, which feasibly applied at the bedside, proved to be accurate to predict independence to walk at three and six months after the stroke. This knowledge is useful for clinical decision making in stroke hospital units.